Diseño de un sistema de gestión de seguridad y salud ocupacional para la empresa de servicio logístico automotriz externa s.a. en la ciudad de quito, basado en la normativa legal ecuatoriana vigente. - Medina Pacheco, Vanesa Rosaly (2016)
This research has the general objective: To make a design Management System Occupational Safety and Health for the company Automotive Logistics Service External S.A., based on current legislation; whose specific objectives are: • Describe the initial situation on regulatory compliance enterprise SSO. They have been treated in the first chapter. • Identify the activities and managed by EXTERNAL S.A., processes regarding the risks. This objective is developed in the assessment and risk management. • Develop design Management System Occupational Safety and Health. To fulfill this objective has been developed in the proposal made This work is an answer to the problem is: How External S.A. company can keep focused on health and safety control? Descriptive methodology was used with inductive deductive method for the development of the fundamental categories.